Economic consequences of implementing and communicating value based management systems. (18th December 2017) - Schultze, Wolfgang; List, Thomas; Schabert, Bettina; Dinh, Tami
Abstract: We study the consequences of implementing and communicating Value Based Management (VBM) systems on information asymmetries and the cost of capital. We analyse the firms' reporting on internal control systems as the source of information for market participants. In addition, literature posits that improving communications with shareholders by providing additional information on value generation (Value Based Reporting, VBR) is an integral part of implementing VBM. We find that the implementation of VBM and the extent of VBR are, both individually and jointly, significantly related to lower information asymmetries and lower cost of capital. We find a slight moderation of the effect of VBM by VBR. For increasing VBR, we find that information asymmetries and cost of capital decrease more strongly for firms without implemented VBM systems. This indicates that VBR can to some extent substitute VBM. Overall, however, firms using a combination of VBM and VBR attain lower levels of information asymmetry and cost of capital. We provide evidence for the real effects of disclosure, suggesting that disclosures on internal control systems serve as a governance mechanism, reducing information asymmetries and the cost of capital by aligning shareholders' and managers' interests.